The role of intellectual capital in the performance of universities in Medan - Delyana Rahmawany Pulungan; Murviana Koto (Proceedings of AICS - Social Sciences, 2017)
The main purpose of this research is to find out the relationship of intellectual capital and three components of intellectual capital on the performance of public universities in Medan. Three components of intellectual capital such as human capital, structural capital and relational capital were taken as independent variables and universities’ performance was taken as dependent variable. The population of this research is three public universities in Medan, such as UIN-SU (Universitas Islam Negeri) of North Sumatera, USU (University of North Sumatra) and UNIMED (Universitas Negeri Medan). Sample for this research was 300 respondents, which is collected using convenience sampling technique from lecturers and employees of three public universities in Medan. Structured questionnaires were made as a research instrument to collect data form respondents. Structural Equation Model (SEM) with AMOS were used to test the relationship between components of intellectual capital and universities performance. Results indicate that (1) all the three components show a significant relationship with performance (2) among the three components, the relation of human capital is more prominent on performance of universities.